Visible‐Light‐Induced Metal‐Free Synthesis of 2‐Phosphorylated Thioflavones in Water - Liu, Xiao‐Ceng; Chen, Xiao‐Lan; Liu, Yan; Sun, Kai; Peng, Yu‐Yu; Qu, Ling‐Bo; Yu, Bing (ChemSusChem, 2020)
The introduction of phosphorus functional groups into the skeleton of thioflavones is an attractive task and of great significance. Herein, a metal‐free visible‐light‐induced radical cascade cyclization was developed for the preparation of 2‐phosphorylated thioflavones from methylthiolated alkynones and phosphine oxides. In water as a green reaction medium, a large number of such 2‐phosphorylated thioflavones were prepared, catalyzed by 4CzIPN [1,2,3,5‐tetrakis(carbazol‐9‐yl)‐4,6‐dicyanobenzene] under visible‐light irradiation. These reactions could be performed at ambient temperature and feature simple operation, wide reaction scope, and recyclability of aqueous media. Let there be light: By using water as a reaction medium, a large number of 2‐phosphorylated thioflavones are prepared through the reaction of methylthiolated alkynones and phosphine oxides catalyzed by 4CzIPN [1,2,3,5‐tetrakis(carbazol‐9‐yl)‐4,6‐dicyanobenzene] under visible‐light irradiation.